Interdisciplinarity and self-reflection in civic education - Spanget Christensen, Torben (Nordidactica, 2013)
Focus of interest in this article are the concepts of globalization and civic citizenship and the questions are; what is required to be a global citizen, and how to work with this in civic education. The concept of civic citizenship implies democracy. A citizen is an independent and (to some extent) educated decision maker and actor, not a mere subject loyal to the sovereign. So whenever speaking of a global citizen democracy is implied. But the world is not a democratic place as such. Most of it in fact is quite undemocratic. The question therefore is how it is possible to act as a citizen (as a democrat) in global space. The article argues that this will only be possibly if citizens are capable of dealing with complex societal problems and to understand their own role as citizens (democrats) in relation to these problems. The argument is firstly that problems and issues in global space are complex and can only be understood interdisciplinary. Therefore the ability to reflect problems interdisciplinary is crucial to the global citizen. The second argument is that the ability of self-reflection is necessary for citizens in their efforts to understand, maintain and develop their own (democratic) identity and (democratic) values and practices in relation to the complexity and unfamiliarity of the various non-democratic identities, values and practices in a global space. Therefore it is suggested that students in civic education need to develop competencies of reflection on interdisciplinarity and self-reflection-as-citizen as key tools for analyzing societal problems and to act democratically on them. And it is suggested that dealing with interdisciplinarity requires use of second order concepts and that self-reflection as citizens requires third order concepts